A IMPLEMENTATION OF INCLUSIVE EDUCATION IN PRIMARY SCHOOLS: A LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Muslimah, Revi; Darmayanti, Mela (Jurusan Pendidikan Luar Biasa, 2024)
Inclusive education has become the main focus in supporting successful learning for all students, especially those with special needs. This research aims to investigate the implementation of inclusive education in elementary schools. This research uses literature review and bibliometric methods with the help of the publish or perish application and Google Scholar with the keywords